2019
DOI: 10.2174/1871520619666190405112507
|View full text |Cite
|
Sign up to set email alerts
|

Punicic Acid Inhibits Glioblastoma Migration and Proliferation via the PI3K/AKT1/mTOR Signaling Pathway

Abstract: Background: Punicic Acid (PA) is a polyunsaturated fatty acid that accounts for approximately 70%- 80% of Pomegranate Seed Oil (PSO). PA possesses strong antioxidant, anti-inflammatory, anti-atherogenic effects, and anti-tumorigenic properties. Pomegranate extracts have been shown to have anticancer activity in many studies. However, there is no evidence for the effect of PSO on T98 glioblastoma cells. Therefore, the present study was the first to investigate the mechanisms induced by PA on T98 cells, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…In addition to inhibiting the proliferation of tumor cells, this study also demonstrated that nobiletin inhibited the migration and invasion of renal cancer cells. Earlier studies have shown that inhibition of Akt expression suppressed cell migration (23)(24).The results of this study indicate that nobiletin inhibited the activation of Akt, which may be one of the mechanisms by which nobiletin inhibited the invasion and migration of renal cancer cells.…”
Section: Nobiletin Inhibited the Invasion Of Renal Cancer Cellssupporting
confidence: 61%
“…In addition to inhibiting the proliferation of tumor cells, this study also demonstrated that nobiletin inhibited the migration and invasion of renal cancer cells. Earlier studies have shown that inhibition of Akt expression suppressed cell migration (23)(24).The results of this study indicate that nobiletin inhibited the activation of Akt, which may be one of the mechanisms by which nobiletin inhibited the invasion and migration of renal cancer cells.…”
Section: Nobiletin Inhibited the Invasion Of Renal Cancer Cellssupporting
confidence: 61%
“…Notably, this was also observed for the highly invasive ACHN cells, which are derived from pleural effusion metastasis. Earlier studies have shown that activating AKT inhibition can suppress cell migration (Marcial-Medina et al, 2019; Mete et al, 2019). Our own results indicated that nobiletin inhibits AKT activation, suggesting that this could be one of the mechanisms underlying the inhibitory effect of nobiletin on the invasion and migration of renal carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, punicic acid was regulated upon FMT. The potent anti-tumor effect of punicic acid might play a role in tumor control (39, 40). Lastly, the abundance of several amino acids was also decreased in the plasma, including glycine, serine, and cysteine ( Fig.…”
Section: Discussionmentioning
confidence: 99%